Controlled study on thymol + eugenol vaginal douche versus econazole in vaginal candidiasis and metronidazole in bacterial vaginosis - Sosto, Francesco; Benvenuti, Claudio; null (Arzneimittelforschung, 2011)
Bacterial vaginosis (BV) and vaginal candidiasis (VC) are usually managed with topical antibiotics. This study compared the efficacy of a thymol + eugenol vaginal douche (SD) (CAS nr. thymol: 89-83-8 and eugenol: 97-53-0), with econazole (CAS 27220-47-9) in VC and metronidazole (CAS 443-48-1) in BV, as suppository reference therapies. Thymol and eugenol are natural antibacterial and antimycotic active ingredients extracted from plants.A multicentre, parallel group, randomized study was performed, after stratification for diagnosis. Twenty-three Italian gynaecological units enrolled 459 patients (232 BV, 227 VC). The treatments applied were as follows: SD 1 douche/day (Saugella lavanda Attiva®) for 1 week, 1 metronidazole vaginal suppository/night for 1 week and 1 econazole vaginal suppository/night for 3 days. Clinical evaluations were performed before and 1 week after treatment.A similar significant symptom reduction was observed with metronidazole and SD in BV and with econazole and SD in VC.SD was found to be an effective prescription drug in minor recurrent vaginal infectious episodes and its use can reduce the repeated exposure to antibiotics.
Keywords: Bacterial vaginosis; Eugenol; Plant extracts; Thymol; Vaginal candidiasis; Vaginal douche